Optimization of ETLE by the Law Enforcement Traffic Police Unit of Surakarta Police Resort to Minimize Traffic Violations - Vidyatama, Rahmandika Shantya (Advances in Police Science Research Journal, 2024)
Traffic has an important and central role in achieving the needs of society, but on the other hand it also causes various problems related to traffic law violations, accidents, road user irregularities and congestion. ETLE (electronic traffic law enforcement) is a good step for the police to realize public services that are more effective, efficient, transparent and accountable. This essay intends to analyze the implementation of the organizational resources of the Law Enforcement Unit of the Surakarta Traffic Police Unit in law enforcement with ETLE, as well as its operational management with the aim of minimizing traffic violations. The theories and concepts in this study use law enforcement theory, organizational resource theory and management theory. This research uses a qualitative descriptive method whose main data are primary sources, namely interviews, actions and also additional data such as supporting documents and articles. The research was conducted at Surakarta Police Station. The results of this study indicate that the organizational resources of the Surakarta City Police Traffic Unit in enforcing the law with ETLE are said to be still not optimal because the law enforcement budget is still insufficient, there are still infrastructure problems, ETLE limitations in capturing visible violations only. Then for operational management of ETLE law enforcement by Surakarta City Police Traffic Unit it is said to be quite optimal. In accordance with the discussion analyzed by the POAC management process, both planning, organizing, actuating to controlling have been carried out optimally by Traffic law enforcement unit of Surakarta City Police Department.